2018
DOI: 10.1371/journal.pone.0209020
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent cytotoxicity of silver nanoparticles to Azotobacter vinelandii: Growth inhibition, cell injury, oxidative stress and internalization

Abstract: The influence of nanomaterials on the ecological environment is becoming an increasingly hot research field, and many researchers are exploring the mechanisms of nanomaterial toxicity on microorganisms. Herein, we studied the effect of two different sizes of nanosilver (10 nm and 50 nm) on the soil nitrogen fixation by the model bacteria Azotobacter vinelandii. Smaller size AgNPs correlated with higher toxicity, which was evident from reduced cell numbers. Flow cytometry analysis further confirmed this finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 72 publications
4
69
1
Order By: Relevance
“…DNA damages, such as mutations, deletions, single-strand breaks, double-strand breaks, and cross-linking with proteins, may occur [168]. Zhang et al revealed that damaging cell membrane and generating ROS are involved in the antibacterial mechanisms [169]. They observed damage of cell membrane and AgNPs inside Azotobacter vinelandii cells using TEM and revealed AgNP-induced hydroxyl radicals inside bacterial cells using electron spin resonance.…”
Section: Mechanisms Of Action Of Nanoparticles Against Phytopathogensmentioning
confidence: 99%
“…DNA damages, such as mutations, deletions, single-strand breaks, double-strand breaks, and cross-linking with proteins, may occur [168]. Zhang et al revealed that damaging cell membrane and generating ROS are involved in the antibacterial mechanisms [169]. They observed damage of cell membrane and AgNPs inside Azotobacter vinelandii cells using TEM and revealed AgNP-induced hydroxyl radicals inside bacterial cells using electron spin resonance.…”
Section: Mechanisms Of Action Of Nanoparticles Against Phytopathogensmentioning
confidence: 99%
“…Currently, nanostructures (NS) containing some of these non-essential metals are used in diverse applications such as water treatment, photocatalysis, optics and therapeutic procedures, among others [5,17]. In particular, gold nanostructures (AuNS) behave as potent antimicrobial agents against multidrug resistant Gram-negative and Gram-positive bacteria [18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, gold nanostructures (AuNS) behave as potent antimicrobial agents against multidrug resistant Gram-negative and Gram-positive bacteria [18]. In general, it has been suggested that AuNS would be toxic because they can generate ROS, similar to that seen in many other antibacterial materials such as ZnO, TiO 2 and Ag nanoparticles (NPs) [17,19,20]. Other targets depend on the route of gold(III) complexes synthesis or composition; for instance, AuNPs covered with organic molecules such as 4,6-diamino-2-pyrimidinethiol produce i) a change in membrane potential that limits ATPase activity and ii) inhibit tRNA binding to the ribosome, thus leading to a collapse of several biological processes without ROS production [21].…”
Section: Introductionmentioning
confidence: 99%
“…The adherence of silver ions to the bacterial cell wall can also cause cell wall destruction and release of essential cellular components [41]. Due to the high affinity of silver to sulfur, nitrogen and oxygen, silver ions can bind to sulfhydryl groups in proteins and cause protein denaturation or bind to N atoms from nucleic acids and prevent DNA replication [42].…”
Section: Silver and Silver Nanoparticlesmentioning
confidence: 99%